(3dhYI GdTGcj hOeYI GdHGcjs - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s
(3ChdgG (B:s
(3hdGHO ef Tchi Edi Pj eQhAI jhGSjc Cf jSdjc Ch jJhLY s
(3BNQgG (B:s
(3YSi GddjGdj, GdJj (B[(3CVfJ(B] (3HaQbJfG LSej, SJLeYfj jhekG hJLeYg hgG CfG CQLh YhO GdhUGd, hHdhZ Gdefi hGdBeGd s
(3Vef eLehY , JQJjHgG (B: (3ef U (B309 - (3U(B384s
(3hgj ebGeIs
(3hHgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B114 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B352s
Keywords: (3GdCOHs